2017
DOI: 10.18553/jmcp.2017.23.2.136
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effect of Cancer Treatment on Work Productivity of Patients and Caregivers

Abstract: This study was funded by Novartis Pharmaceuticals, which provided the concept, general oversight, and research collaboration on the project. Covvey and Kamal received research funding from Novartis Pharmaceuticals and the College of Psychiatric and Neurologic Pharmacists. Zacker is employed by, and owns stock in, Novartis Pharmaceuticals. A related poster abstract was presented at the Academy of Managed Care Pharmacy April 2016 Annual Meeting and published as Kamal KM, Covvey JR, Dashputre A, Ghosh S, Zacker C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 71 publications
4
70
1
4
Order By: Relevance
“…However, 80% of overall productivity loss was due to patients feeling unable to return to work post‐ASCT, with many stating that they lacked the fitness to conduct daily duties effectively. These findings support a recent international systematic review of productivity loss across a broad range of cancers, including leukaemia, which highlighted that productivity losses were often associated with disease progression and patients feeling unable to carry out their previous roles …”
Section: Discussionsupporting
confidence: 87%
“…However, 80% of overall productivity loss was due to patients feeling unable to return to work post‐ASCT, with many stating that they lacked the fitness to conduct daily duties effectively. These findings support a recent international systematic review of productivity loss across a broad range of cancers, including leukaemia, which highlighted that productivity losses were often associated with disease progression and patients feeling unable to carry out their previous roles …”
Section: Discussionsupporting
confidence: 87%
“…Types of outcomes: The outcome of interest was work productivity including absenteeism, presenteeism, loss of work productivity, work impairment, sick leave, missed work, time away from work, work ability, short‐term disability, use of ancillary services, workforce dropout, employment, and long‐term disability …”
Section: Methodsmentioning
confidence: 99%
“…Recent systematic and scoping reviews have reported that cancer negatively affects the employment of spouses of patients with cancer in terms of decreased productivity and work absences. Although a few studies have estimated how decreased productivity and work absences translate into spouses' wage losses, most have focused on cancers other than breast cancer or mixed groups including breast cancer with varying disease stages or only advanced disease, and this makes it impossible to isolate specifically the effect of nonmetastatic breast cancer on spouse wage losses.…”
Section: Introductionmentioning
confidence: 99%